2021
DOI: 10.1371/journal.pone.0260070
|View full text |Cite
|
Sign up to set email alerts
|

Water-seeking behavior among terrestrial arthropods and mollusks in a cool mesic region: Spatial and temporal patterns

Abstract: Dehydration can have negative effects on animal physiological performance, growth, reproduction, and survival, and most animals seek to minimize these effects by reducing water losses or seeking water sources. Much—but not all—of the research on animal water balance comes from dryland ecosystems. However, animals inhabiting mesic regions may also experience desiccating conditions, for example within urban heat islands or during heatwaves and droughts. Here we examined how spatial variation in impervious surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Several studies have found reduced activity of rainforest ants, beetles and termites during heavy rain (Basu, 1997 ; Dibog et al, 1998 ; Farji‐Brener et al, 2018 ; Grimbacher & Stork, 2009 ) and in Panamanian rainforest, aerial insects shifted activity from canopy gaps during the wet season to forest understory during the dry season (Richards & Windsor, 2007 ). High VPD can influence behavior (Becker et al, 2021 ), and in arid systems arthropods often seek moist refugia and enter dormancy (Denlinger, 1986 ). We found effects of rainfall were weaker for sampling methods with clear changes in activity such as greater numbers of aerial and leaf‐litter taxa during sunny, warm periods.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found reduced activity of rainforest ants, beetles and termites during heavy rain (Basu, 1997 ; Dibog et al, 1998 ; Farji‐Brener et al, 2018 ; Grimbacher & Stork, 2009 ) and in Panamanian rainforest, aerial insects shifted activity from canopy gaps during the wet season to forest understory during the dry season (Richards & Windsor, 2007 ). High VPD can influence behavior (Becker et al, 2021 ), and in arid systems arthropods often seek moist refugia and enter dormancy (Denlinger, 1986 ). We found effects of rainfall were weaker for sampling methods with clear changes in activity such as greater numbers of aerial and leaf‐litter taxa during sunny, warm periods.…”
Section: Discussionmentioning
confidence: 99%
“…Insects and other arthropods employ a variety of behavioral approaches to avoid or cope with dehydration, and these activities have profound impacts on trophic interactions. Under desiccating conditions, arthropods may either seek out additional water sources (e.g., 6,45,92,140) or seek refugia that lower water loss rates (32,89). When terrestrial arthropods seek water sources, in some cases, the only available water is within food, resulting in increases in consumption of vegetation by herbivores or prey by predators (89).…”
Section: Connecting Behavioral Responses To Dehydration and Trophic I...mentioning
confidence: 99%
“…Terrestrial mollusks are an ecological group of creatures that makes up about 35,000 modern species. They belong to the Gastropoda class and are an important part of many ecosystems as they process much of the dead organic matter, distributing some substances and forming the diet basis for many animals (Köse et al, 2015;Peña et al, 2017;Cilia & Fratini, 2018;Becker et al, 2021).…”
Section: Introductionmentioning
confidence: 99%